The Effectiveness of Behavioural Activation Intervention in Depression Symptoms among UNJ Student - Zakiah, Ernita (Journal of Research and Measurement in Psychology: JPPP, 2019)
This study aims to examine the effect of Behavioral Activation (BA) to reduce student's depression disorders of Universitas Negeri Jakarta. Methods of data collection using observations, semi-structured interviews, and BDI measurement tools. The measuring instrument used is the Beck Depression Inventory (BDI) made by Beck in (1976) translated by Zarina (2007). Interference disorders need to be given an intervention, because subjects with depressive disorders tend to avoid social environment, easily feel tired, avoid or do nothing activities, almost all the time experiencing feelings of depression, easily distracted concentration, etc.